PENENTUAN pH OPTIMUM ISOLASI KARAGINAN DARI RUMPUT LAUT JENIS Eucheuma cottonii - Bawa, I G. A. G.; Bawa Putra, A. A.; Ratu Laila, Ida (Jurnal Kimia (Journal of Chemistry), 2012)
This research aimed to determine the optimum pH for the isolation carrageenan from Eucheuma cottonii seaweed. The isolation was conducted at various pH : 7.5, 8.0, 8.5, and 9.0. A TLC using methanol : water (5:1) as mobile phase from standard carrageenan, gave result on Rf value 0.74 as equal to sample on treatment condition at pH 8.0 and 8.5. whereas, sample on treatment condition at pH 7.5 and 9.0 gave Rf value 0.72. In using ethanol : water (3:1) as mobile phase gave result on Rf value 0.75 from both standard and sample treated at 7.5, 8.0, and 8.5, while at pH 9.0 gave Rf value 0.74. Melting point test from standard gave range value 240-242, while for sample on treatment condition at pH 7.5, 8.0, 8.5, and 9.0 gave range value each such 242-244, 241-243, 240-242, and 240-243. Compounds identification with solubility test method using various solvent medium obviously showed that both of standard and sample from various treatment condition were insoluble such as in aquades 200C, NaCl 25% 200C and 800C, saccharosse 65% 200C and chloroform. Otherwise, they were soluble in aquades and saccharosse 65% with temperature 800C. Infrared spectrum standard compound and sample from various treatment condition indicated that they were identical. Carrageenan isolation produce the largest number of rendemen at pH 8.5 with about 34.65%, while the variant of carrageenan isolate was classified by kappa carrageenan.
Keywords: seaweed, Eucheuma cotonii, isolation, optimum pH, carrageenan